2015
DOI: 10.3109/14756366.2015.1088841
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the inhibitory activity of Withaferin-A against Pteridine reductase-1 of L. donovani

Abstract: Withaferin A is an abundant withanolide present in Withania somnifera leaves and to some extent in roots. It has been known for its profound anti-cancer properties, but its role in counteracting the Leishmania donovani infection has to be explored. Pteridine reductase 1 (PTR1) is involved in pteridine salvage and an important enzyme for the parasite growth, which could be targeted for the development of an efficient antileishmanial drug. We employed molecular docking studies to identify the binding mode of wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Due to the lack of purified DHFR-TS enzyme, the current study could not include enzyme assay. However, enzyme assayed from parasite lysate with WA has shown the inhibition activity reported earlier [ 45 ].…”
Section: Main Textmentioning
confidence: 75%
See 1 more Smart Citation
“…Due to the lack of purified DHFR-TS enzyme, the current study could not include enzyme assay. However, enzyme assayed from parasite lysate with WA has shown the inhibition activity reported earlier [ 45 ].…”
Section: Main Textmentioning
confidence: 75%
“…Recently, we reported that WA inhibits Ld PTR1 enzyme activity and molecular docking studies of WA showed high binding affinity with PTR1. Enzyme assay with purified PTR-1 revealed that WA inhibits enzyme activity through uncompetitive mode [ 45 ]. The present molecular docking study reveals that the binding energy of WA with Ld DHFR-TS is higher than Hu DHFR, Hu TS enzymes and WA inhibits Ld DHFR-TS same as the PTR-1 enzyme.…”
Section: Main Textmentioning
confidence: 99%
“…Our current finding of Leishmania-activated C kinase protein interacting with the macrophage membrane protein, strongly backed by previous studies, indicated this as an important molecule to explore as a potential target for chemotherapeutic intervention. Withaferin A (WA), an inhibitor of activated C kinase and other enzymes of Leishmania, significantly reduced the proliferation of L. donovani to macrophages, highlighting its role in the host-parasite interaction [31,32]. Leishmania-activated C kinase (LACK) facilitates the cytochrome c oxidase subunit expression to promote the fitness of L. major.…”
Section: Discussionmentioning
confidence: 99%
“…Another important enzyme that can be targeted for developing an effective anti-leishmanial drug is Pteridine reductase 1(PTR1). The molecular docking studies of WA against PTR 1 showed the binding efficacy with lowest binding energy of -6.73kJ/mol (Chandrasekaran et al, 2015). Due to structural similarity between the PTR1 and DHFR-TS, the inhibitor that targets PTR1 can also target DHFR-TS.…”
Section: Anti-microbial Activitymentioning
confidence: 99%